Evaluation of Antioxidant and Antimicrobial Properties of Lemon and Pomegranate - Md. Usman, Md. Rageeb; Upasani, Mansi Prasad; Shaikh, Mohammed Zuber (Journal of Neonatal Surgery, 2025)
Antioxidant is deﬁned as any substance that prevents oxidation of the substrate. This study was aimed at assessing the effect of Pomegranate and lemon antioxidant and antimicrobial properties. various components present in lemon and pomegranate shows antioxidant and antimicrobial properties determine according to various study’s. Citrus fruit is a rich source of bioactive chemicals, little is known about the possible health benefits of the seeds. This study investigates the antioxidant and antibacterial parcels of Citrus Ten. & Pasq. (Family Rutaceae) seeds excerpts as well as their ingredients, to identify implicit operations for this underutilized resource (phytochemical study of bomb seed). Skin conditions similar as dermatitis, prurigo, and scabies present a major health concern in the Eastern Cape, South Africa, where there's a failure of dermatologists, compounded by the fact that utmost dermatologists are centered near civic areas and are not accessible to 70 of the pastoral population. The loftiest antibacterial exertion was attained with the acetone excerpt of C. limon against Enterococcus faecalis and Bacillus subtilis, and the most susceptible bacteria grounded on the overall mean inhibition compasses were the gram-negative Salmonella typhimurium, Shigella sonnei and the gram-positive E. faecalis and B. subtilis. Pomegranate is an important source of bioactive composites and has been used for folk drug for numerous centuries. Pomegranate juice has been demonstrated to be high in antioxidant exertion and is eﬀective in the forestallment of atherosclerosis. In a study it’s set up that pomegranate peel had the loftiest antioxidant exertion among the peel, pulp and seed fragments. The peels uprooted from colorful citrus species are a major source of phenols, flavonoids and anti-microbial agents.